Suffer strong : how to survive anything by redefining everything - Wolf, Katherine (Stroke victim); Wolf, Jay (Zondervan, 2020)
"Profoundly inspiring, compellingly vulnerable, and surprisingly funny, Suffer Strong offers readers the hard-won insights of beloved authors Katherine and Jay Wolf and incorporates practical strategies for weathering suffering and embracing resilience with winsomeness and joy"--